Kepastian Hukum Pengaturan Penggunaan Tenaga Kerja Asing di Indonesia - Risky Vista Puspitasari; Aries Harianto; Ida Bagus Oka Ana (Lentera Hukum, 2018)
The 1945 Constitution of the Republic of Indonesia states that every citizen has the right to work and a decent life. As a consequence, citizens have the right to receive salary and fair treatment in employment relations. The state has a constitutional responsibility to guarantee the fulfillment of the right to work of migrant and foreign workers in order to provide protection and legal certainty between them. Meanwhile, the national labor law and government regulations on migrant workers only include professional workers. In fact, foreign workers in Indonesia are not only professional workers but also unskilled laborers. Such paradox emerges after the amendment of the regulation of foreign workers which frees and tightens foreign workers in Indonesia. Keywords: Foreign Workers, Right to Work, Legal Certainty